Tax treatment of research and development : a comparative survey of national fiscal measures and of their impact on research - Hoorn, Jacobus van ([Paris] Organisation for Economic Cooperation and Development, 1962)
The book is an objective description of those tax measures which in one way or another affect research. It also stresses on country reports that contain data which are specific to interest to the tax expert.
Prepared at the request of the OECD.
sju 25/01/2019
Loans
Keywords: Research, Industrial; Tax treatment; Research development